(untitled) (Bangladesh Journal of Medical Science, 2019)
Objective: The study was done to determine the effect of Tocotrienol rich fraction (TRF) on the expression of RNAs in C. elegans under oxidative stress. Methods: The nematodes were divided into 4 groups and treated accordingly: control; TRF; hydrogen peroxide (H202); TRF treatment before and after H202-induction (TRF+H202+TRF). Expressions of RNAs were analyzed with Affymetrix Genechip C. elegans Genome Array and Genespring GX11 software where differentially expressed genes were further analyzed using gene ontology (GO). Selected genes (unc-15, cit-1.2, ftn-1, rsks-1, unc-4 and daf-12) were analyzed with RT-qPCR to validate the results. Results: TRF modulated the expression of 314 genes involved in determination of adult lifespan, regulation of growth and lipid modification. A total of 440 genes involved in RNA metabolic processes, transcription, growth and differentiation of muscle and nerve cells were differently expressed following H202 induction. TRF treatment before and after H202- induction resulted in 438 differentially expressed genes involved in RNA metabolic processes, transcription, response to xenobiotic stimulus and protein amino acid phosphorylation. Conclusion: TRF modulates the expression of genes involved in the regulation of lifespan in C. elegans. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.711-721